Effects of creatine supplementation on cardiac autonomic functions in bodybuilders - Mert, Kadir Uğur; Ilgüy, Serdar; Dural, Muhammet; Mert, Gurbet Özge; Özakin, Engin (Pacing and clinical electrophysiology, 2017)
Bodybuilder‐type workouts may affect heart rate variability (HRV), which has considerable potential to assess the role of autonomic nervous system (ANS). A scientifically designed approach is necessary for bodybuilders to achieve better results while protecting their health. In this study, we aimed to investigate HRV parameters in bodybuilders compared to healthy control subjects and effects of creatine supplementation. A total of 48 male participants (16 controls, 16 supplement (–), 16 supplement (+)) were evaluated in our study. Bodybuilders who were taking creatine supplementation were enrolled in supplement (+) group. HRV parameters were measured from 24‐hour Holter recordings of all participants. When mean heart rates were compared with control group (71.5 ± 12.6 beats/min), statistically significant difference was revealed in supplement (–) group (61.8 ± 6.8 beats/min; P = 0.022) unlike supplement (+) group (69.63 ± 14.1 beats/min; P = 0.650). HRV analyses revealed significant parasympathetic shift in supplement (–) group. No significant difference was demonstrated on HRV parameters, except high frequency (P = 0.029) in supplement (+) group. Conclusively, elevated parasympathetic modulation, which is favorable cardiovascular outcome of exercise, was demonstrated in bodybuilders. However, our study also revealed that creatine supplementation attenuates this favorable effect in ANS by limiting elevation of parasympathetic modulation. Although the sympathetic slight shift is attributed to creatine supplementation, it cannot be discriminated from the effects of over training.